Feminizing Wolbachia endosymbiont disrupts maternal sex chromosome inheritance in a butterfly species. Issue 5 (31st October 2017) - Kageyama, Daisuke; Ohno, Mizuki; Sasaki, Tatsushi; Yoshido, Atsuo; Konagaya, Tatsuro; Jouraku, Akiya; Kuwazaki, Seigo; Kanamori, Hiroyuki; Katayose, Yuichi; Narita, Satoko; Miyata, Mai; Riegler, Markus; et al.
Abstract: Wolbachia is a maternally inherited ubiquitous endosymbiotic bacterium of arthropods that displays a diverse repertoire of host reproductive manipulations. For the first time, we demonstrate that Wolbachia manipulates sex chromosome inheritance in a sexually reproducing insect. Eurema mandarina butterfly females on Tanegashima Island, Japan, are infected with the w Fem Wolbachia strain and produce all‐female offspring, while antibiotic treatment results in male offspring. Fluorescence in situ hybridization (FISH) revealed that w Fem‐positive and w Fem‐negative females have Z0 and WZ sex chromosome sets, respectively, demonstrating the predicted absence of the W chromosome in w Fem‐infected lineages. Genomic quantitative polymerase chain reaction (qPCR) analysis showed that w Fem‐positive females lay only Z0 eggs that carry a paternal Z, whereas females from lineages that are naturally w Fem‐negative lay both WZ and ZZ eggs. In contrast, antibiotic treatment of adult w Fem females resulted in the production of Z0 and ZZ eggs, suggesting that this Wolbachia strain can disrupt the maternal inheritance of Z chromosomes. Moreover, most male offspring produced by antibiotic‐treated w Fem females had a ZZ karyotype, implying reduced survival of Z0 individuals in the absence of feminizing effects of Wolbachia . Antibiotic treatment of w Fem‐infected larvae induced male‐specific splicing of the doublesex ( dsx ) gene transcript, causing an intersex phenotype. Thus, the absence of the female‐determining W chromosome in Z0 individuals is functionally compensated by Wolbachia ‐mediated conversion of sex determination. We discuss how Wolbachia may manipulate the host chromosome inheritance and that Wolbachia may have acquired this coordinated dual mode of reproductive manipulation first by the evolution of female‐determining function and then cytoplasmically induced disruption of sex chromosome inheritance.